Economic Extension of Transmission Line in Deregulated Power System for Congestion Management - Kumar, Pravin (Journal of Advanced College of Engineering and Management, 2018)
The chances of congestion in deregulated market are quite high as compared to the monopolistic market as the customers would like to purchase electricity from cheapest available sources. Ways for Congestion management are: Generation rescheduling, Interruptible load curtailment, Transmission system expansion etc. Transmission expansion planning is the last way for congestion management if congestion is not managed by Generation rescheduling and Interruptible load curtailment. A high mean of Locational marginal price (LMP) at a bus indicates no access to cheap generation and a low mean of LMP indicates access to excess cheap generation and no access to enough loads.  Hence, constructing a new line between two buses with low and high mean of LMP will allow the dispatch of the excess cheap generation and flow of energy from low LMP bus to high LMP bus due to price potential difference. Consequently, the flatness of price profile is improved. The final plan is selected by economic analysis.Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 49-54